Novel self‐gelling injectable hydrogel/alpha‐tricalcium phosphate composites for bone regeneration: Physiochemical and microcomputer tomographical characterization. Issue 3 (29th November 2017) - Douglas, Timothy E. L.; Schietse, Josefien; Zima, Aneta; Gorodzha, Svetlana; Parakhonskiy, Bogdan V.; KhaleNkow, Dmitry; Shkarin, Roman; Ivanova, Anna; Baumbach, Tilo; Weinhardt, Venera; Stevens, Christian V.; Vanhoorne, Valérie; et al.
Abstract: Mineralized hydrogels are increasingly gaining attention as biomaterials for bone regeneration. The most common mineralization strategy has been addition of preformed inorganic particles during hydrogel formation. This maintains injectability. One common form of bone cement is formed by mixing particles of the highly reactive calcium phosphate alpha‐tricalcium phosphate (α‐TCP) with water to form hydroxyapatite (HA). The calcium ions released during this reaction can be exploited to crosslink anionic, calcium‐binding polymers such as the polysaccharide gellan gum (GG) to induce hydrogel formation. In this study, three different amounts of α‐TCP particles were added to GG polymer solution to generate novel, injectable hydrogel‐inorganic composites. Distribution of the inorganic phase in the hydrogel was studied by high resolution microcomputer tomography (µCT). Gelation occurred within 30 min. α‐TCP converted to HA. µCT revealed inhomogeneous distribution of the inorganic phase in the composites. These results demonstrate the potential of the composites as alternatives to traditional α‐TCP bone cement and pave the way for incorporation of biologically active substances and in vitro and in vivo testing. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 822–828, 2018.